A novel approach for quantitative determination of cellulose content in tobacco via 2D HSQC NMR spectroscopy. (April 2023) - Tian, Dayu; Huang, Lan; Zhang, Zhao; Tian, Zhenfeng; Ge, Shaolin; Wang, Chenghui; Hu, Yonghua; Wang, Ying; Yang, Jun
Abstract: Cellulose is an important component of tobacco ( Nicotiana tabacum L.) cell walls, which can be precursors for many harmful compounds in smoke. Traditional cellulose content analysis methods involve sequential extraction and separation steps, which are time-consuming and environmentally unfriendly. In this study, a novel method was first introduced to analyze cellulose content in tobacco via two-dimensional heteronuclear single quantum coherence (2D HSQC) NMR spectroscopy. The method was based on derivatization approach to allow the dissolution of insoluble polysaccharide fractions of tobacco cell walls in DMSO‑ d 6 /pyridine- d 5 (4:1 v/v) for NMR analysis. The NMR results suggested that besides the main NMR signals of cellulose, partial signals of hemicellulose including mannopyranose, arabinofuranose, and galactopyranose units could also be identified. In addition, the utilization of relaxation reagents has proved to be an effective way to improve the sensitivity of 2D NMR spectroscopy, which was beneficial for quantification of biological samples with limited quantities. To overcome the limitations of quantification using 2D NMR, the calibration curve of cellulose with 1, 3, 5-trimethoxybenzene as internal reference was constructed and thus the accurate measurement of cellulose in tobacco was achieved. Compared with the chemical method, the interesting method was simple, reliable, and environmentally friendly, which provided a new insight for quantitative determination and structure analysis of plant macromolecules in complex samples. Graphical abstract: Image 1 Highlights: 2D HSQC NMR method for determination of cellulose content in tobacco was simple, reliable and environmentally friendly. Derivatization method was utilized to allow the complete dissolution of cellulose in DMSO‑ d 6 /pyridine- d 5 . One approach by using relaxation reagents to enhance sensitivity of 2D HSQC NMR experiments was simple and effective. The developed 2D HSQC NMR was a good alternative method for qualitative and quantitative analysis of plant macromolecules.